أضرار السحر المادية والمعنوية ووسائل الحد من انتشاره: دراسة مقاصدية = Material and spiritual harms of magic and effective ways of limiting its spread: a higher objectives’ study - Alshareef Mustafa Muhamed, Sedrah; Almushaifri, Yaqoob Ali Saleem; Ghalia, Bouhedda (IIUM Press, International Islamic University Malaysia, 2019)
Objectives of Shariah (maqāṣid). These aims are rarely examined in the Islamic literature on sorcery. The dissertation investigates the development and role of sorcery in ancient societies before highlighting the responsibility of sorcerers for the harm they cause in society. The Objectives of Shariah were used to underline the dangers of sorcery and how it undermines the five necessities of these Objectives. The researcher has followed the inductive approach in tracing and researching relevant topics in original and secondary sources and references, before following the analytical approach to study these sources and references and to analyse the text of interviews. In this regard, the researcher has followed the approach of field studies by conducting interviews with specialist Quranic healers to pinpoint the reality and harm of sorcery and to limit its reach through Islamic, sociological, educational and legal means. Some of the conclusions reached by the researcher includes the fact that sorcery is real and has real effects on individuals and societies. **************************************************************************** يهدف هذا البحث إلى دراسة الأضرار المادية والمعنوية للسحر، وبيان الأحكام الشرعية المتعلقة بذلك في ضوء مقاصد الشريعة. وبينت الدراسة مسؤولية الساحر عن إلحاق الضرر بالمجتمع، مبينا أثر السحر في تفويت حفظ المقاصد الخمسة الضرورية، وقد اتبع الباحث المنهج الاستقرائي في تتبع مباحث الموضوع وقضاياه في المصادر والمراجع، والمنهج التحليلي في تحليل المادة المستقرأة وبيان نصوص المقابلات، إضافة إلى الدراسة الميدانية من خلال إجراء مقابلات مع بعض الرقاة الشرعيين المتخصصين؛ لإبراز واقع حقيقة السحر وأضراره على المسحور، ومعالجة انتشاره معالجة شرعية واجتماعية وتربوية وقانونية؛ لمنعه ومعاقبة الساحر والمترددين إليه.